Peningkatan Keterampilan Meronce dengan Menggunakan Metode Demonstrasi Pada Siswa Kelas V SD - Putri, Dian Ramadhani; yunisrul, yunisrul; Lubis, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Theuse of demonstration methods is one way to solve problems in the learning process. The purpose of this researc his to describe the planning, implementation, and the improvement of skills. This type of researc his class room action research, this study uses a qualitative and quantitative approach that is carriedoutin 2 collaborative cycles between researchers, teachers and fifth grade students, 02 KotoLamo, Kapur IX District, Lima Puluh Kota District. The results of this study indicate anincrease in student skills. The result of meronce cycleI 66.63 in crease din the second cycle 93.5, it can beconcluded that the demonstration method can improvethe skills of dating to fifth grade studentsKeywords: Skills, Meronce, Demonstration Method